A New Method of Combating Corruption in Uzbekistan - Davranov Ulugbek Mirzadavlatovich; Abdujabborov Islomali Umidjon ugli; Eshimov Sulton Akhmadjon ugli (Zien Journals, 2023)
In our country against to fight and in the field new changes and to him against new measures
Keywords: Corruption; population corruption level; Moral corruption; Brilliant collars